Environmental management of waters and riparian areas to protect biodiversity through River Contracts: The experience of Tiber River (Rome, Italy). (28th September 2021) - Caneva, Giulia; Ceschin, Simona; Lucchese, Fernando; Scalici, Massimiliano; Battisti, Corrado; Tufano, Massimo; Tullio, Maria Cristina; Cicinelli, Emanuela
Abstract: Urban rivers may perform important ecological roles and provide many ecosystem services, especially in urban contexts. Considering this, River Contracts were officially introduced in 2000, during the Second Forum of the World Water Council, as participative agreements aimed at managing the complexity of fluvial ecosystems. Collecting data on fluvial and riparian biodiversity, establishing ecological relationships among biological components, and evaluating their resistance and resilience to anthropic impacts are needed to assess the ecological sustainability of the anthropic actions. Here, we provide a review of literature and regulation on River Contracts, and a methodological contribution to the evaluation of different environmental components, their ecological connections, and the role of anthropic impacts. To address the aim, we performed a critical analysis of the existing data on the Tiber River close to Rome. We used the information to identify the actions that should be included in the Tiber River Contract to improve its natural value and its potential ecosystem services. Several areas emerged where information was lacking such as the human impact on these ecosystems. Data highlight the disappearance of rare Mediterranean species and of those linked to wetland habitats, as well as an increase in alien species and species typical of disturbed areas. Further research on biodiversity and management is required to support nature conservation.